Fuzzy Logic Algorithm and GSM IoT Based Fire Fighting Robot - Vasanthkumar, P; Arunraj, P V; Mohammed Bilal Khan, N; Akash, A V; Mukunthan, R.; Harish Babu, R. (Journal of physics. Conference series, 2021)
Artificial Intelligence (AI) covers many areas related to mechanical, electrical, psychology and philosophy. GSM IoT is the new method and idea in a simple application of fire detection. In our project, we are using IR sensor to detect a fire and it sends the information to a microcontroller, which is programed based on a fuzzy logic algorithm that helps to detect the fire and moves the nozzle head of the Fire Fighting Robot. The stepper motor is used for a 360 degree clockwise and anticlockwise rotation. The D.C motor controls the valve opens of the nozzle. The fuzzy logic algorithm is helps to detect the fire and to turn the nozzle in the direction of fire.